Simplifying Service Management with Consul Overcome Connectivity and Security Challenges Within Dynamic Service Architectures. - Jackson, Robert E. (Packt Publishing, Limited, 2021)
Understand the basics of the Consul server and client architecture, and learn how to apply Consul for dynamic and secure service discovery, communication, and network connectivity automation Key Features Discover how Consul servers and clients operate to facilitate primary Consul use cases Learn how Consul dynamically and securely discovers and shares service data throughout the network Utilize Consul to extend and secure network communications across multiple operating environments Book Description Within the elastic and dynamic nature of cloud computing, efficient and accurate service discovery provides the cornerstone for all communications. HashiCorp Consul facilitates this service discovery efficiently and securely, independent of the operating environment. This book will help you build a solid understanding of both the concepts and applications of HashiCorp Consul. You'll begin by finding out what you can do with Consul, focusing on the conceptual views of configuration samples along with Terraform code to expedite lab environment and hands-on experimentation, which will enable you to apply Consul effectively in your everyday lives. As you advance, you'll learn how to set up your own Consul cluster and agents in a single datacenter or location and understand how Consul utilizes RAFT and GOSSIP protocols for communication. You'll also explore the practical applications of primary Consul use cases, including communication flows and configuration and code examples. With that knowledge, you'll extend Consul across datacenters to discuss the applicability of multiple regions, multiple clouds, and hybrid cloud environments. By the end of this Consul book, you will have the tools needed to create and operate your own Consul cluster and be able to facilitate your service discovery and communication. What you will learn Deploy and configure a highly available multi-node Consul architecture Implement Consul service discovery across multiple services Utilize Consul to monitor and communicate service health status Connect services securely across a range of environments Leverage your knowledge of the Consul service to automate network infrastructure Extend your Consul knowledge and connectivity across multiple environments Who this book is for If you are a solutions architect, DevOps engineer, or anyone new to the cloud-native framework looking to get started with using Consul, then this book is for you. Knowledge of Terraform is helpful but not necessary. A basic understanding of networking and Kubernetes systems will help you get the most out of this book.